Preoperative celecoxib use does not increase risk of myocardial infarction and may be protective against thromboembolic complications following total joint arthroplasty - Matthew L. Magruder; Shabnam Parsa; Ariel N. Rodriguez; Mitchell Ng; Che Hang Jason Wong (Journal of Orthopaedic Reports)
Purpose: The purpose of this study was to determine if preoperative celecoxib treatment raises the risk of postoperative 1) myocardial infarctions, 2) thromboembolic complications, 3) acute kidney injuries, 4) transfusions, and 5) readmissions. Materials and methods: Using the administrative claims database, PearlDiver, a retrospective study from January 2010 to October 2020 was conducted. Patients undergoing total knee or hip arthroplasty for osteoarthritis with recent celecoxib prescription were included, excluding those with MI history. Propensity score matched 230,587 patients (TKA: 38,433 celecoxib, 192,154 control; THA: 21,603 celecoxib, 108,008 control). Outcomes evaluated: 90-day myocardial infarction, DVT, PE, VTE, AKIs, transfusion, readmission. Multivariate logistic regression calculated odds ratios, 95 % CIs, p-values. Welch's t-tests assessed differences in stay lengths, costs (p < 0.001 threshold). Results: Celecoxib-treated patients showed comparable postoperative MI rates after TKA (0.16 % vs 0.23 %; OR 0.72; p = 0.018) and THA (0.25 % vs 0.22 %; OR 1.14; p = 0.359) versus controls. In TKA, celecoxib correlated with lower DVT (3.11 % vs 3.25 %; OR 0.95; p < 0.001) and transfusion (5.57 % vs 7.09 %; OR 0.76; p < 0.001) rates. PE (2.56 % vs 2.71 %; OR 0.94; p = 0.106), VTE (4.45 % vs 4.77 %; OR 0.93; p = 0.008), and readmission (5.35 % vs 5.39 %; OR 0.99; p = 0.73) showed no significant difference. In THA, celecoxib linked to lower DVT (2.57 % vs 3.02 %; OR 0.84; p < 0.001), VTE (3.64 % vs 4.30 %; OR 0.83; p < 0.001), transfusion (6.57 % vs 10.09 %; OR 0.65; p < 0.001), and readmission (5.49 % vs 6.06 %; OR 0.89; p = 0.001); PE (2.10 % vs 2.40 %; OR 0.87; p = 0.007) showed no significant difference. Conclusion: Celecoxib use showed no heightened risk of postoperative TKA and postoperative THA myocardial infarctions. Additionally, the celecoxib group exhibited notably reduced or insignificantly different rates of DVT, PE, VTE, transfusions, and readmissions.